2013
DOI: 10.3390/v5030792
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Distribution in the NSP4 Protein in Rotaviruses Isolated from Mexican Children with Moderate to Severe Gastroenteritis

Abstract: The NSP4 protein is a multifunctional protein that plays a role in the morphogenesis and pathogenesis of the rotavirus. Although NSP4 is considered an enterotoxin, the relationship between gastroenteritis severity and amino acid variations in NSP4 of the human rotavirus remains unclear. In this study, we analyzed the sequence diversity of NSP4 and the severity of gastroenteritis of children with moderate to severe gastroenteritis. The rotavirus-infected children were hospitalized before the rotavirus vaccine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Most of the variations in NSP4 aas from E2 strains occurred in the carboxy-terminal region, including the VP4-binding domain, and the same result has been observed in studies comparing NSP4 aas from E1 strains ( González-Ochoa et al 2013 , Fredj et al 2014 ). This finding suggests that NSP4 is involved in viral morphogenesis and that additional studies are necessary to understand how these variations in the NSP4 protein may interfere with the structural conformation of the interaction sites between NSP4 and VP4.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Most of the variations in NSP4 aas from E2 strains occurred in the carboxy-terminal region, including the VP4-binding domain, and the same result has been observed in studies comparing NSP4 aas from E1 strains ( González-Ochoa et al 2013 , Fredj et al 2014 ). This finding suggests that NSP4 is involved in viral morphogenesis and that additional studies are necessary to understand how these variations in the NSP4 protein may interfere with the structural conformation of the interaction sites between NSP4 and VP4.…”
Section: Discussionsupporting
confidence: 69%
“…The phylogenetic tree showed E2 intragenotype variation due to the presence of different branches formed by the strains from the same collection year. The same pattern of intragenotypic variation has been observed in E1 strains in Mexico and the authors attributed this finding to the accumulation of single point mutations in the NSP4 gene ( González-Ochoa et al 2013 ).…”
Section: Discussionmentioning
confidence: 55%
“…Besides, the E1 genotype was the dominant genotype (87% of samples), while the E2 genotype was less frequent (13% of samples). While it seems that E1 and E2 are not the only human genotypes, the diversity of NSP4 genes among human RVAs in some studies is restricted to genotypes E1 or E2 9–11 . In other studies, unusual E‐genotypes in human RVA strains have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The post-2010 strains (lineage II) had lineage-specific aa mutations at residues 141 and 145 within the VP4-binding domain (aa 112–146) and at residue 169 within the double-layered particle (DLP)-binding region (aa 161–175) () [42, 43]. These residues are known to be susceptible to aa variation [44]. Of particular interest, residue 141 showed sequential mutation (valine→alanine→isoleucine→tyrosine) corresponding to changes in the sublineage from lineage Ie to If to IIa to IIb.…”
Section: Discussionmentioning
confidence: 99%